Immunological and Technical Considerations in Application of Alginate-Based Microencapsulation Systems - Paredes Juárez, Genaro Alberto; Spasojevic, Milica; Faas, Marijke M.; de Vos, Paul (Frontiers in Bioengineering and Biotechnology, 2014)
Islets encapsulated in immunoprotective microcapsules are being proposed as an alternative for insulin therapy for treatment of type 1 diabetes. Many materials for producing microcapsules have been proposed but only alginate does currently qualify as ready for clinical application. However, many different alginate-based capsule systems do exist. A pitfall in the field is that these systems are applied without a targeted strategy with varying degrees of success as a consequence. In the current review the different properties of alginate-based systems are reviewed in view of future application in humans. The use of allogeneic and xenogeneic islet sources are discussed with acknowledging the different degrees of immune protection the encapsulation system should supply. Also issues such as oxygen supply and the role of danger associated molecular patterns (DAMPS) in immune activation are being reviewed. A common property of the encapsulation systems is that alginates for medical application should have an extreme high degree of purity and lack pathogen-associated molecular patterns (PAMPs) to avoid activation of the recipient’s immune system. Up to now, non-inflammatory alginates are only produced on a lab-scale and are not yet commercially available. This is a major pitfall on the route to human application. Also the lack of predictive pre-clinical models is a burden. The principle differences between relevant innate and adaptive immune responses in humans and other species are reviewed. Especially the extreme differences between the immune system of non-human primates and humans are cumbersome as non-human primates may not be predictive of the immune responses in humans, as opposed to the popular belief of regulatory agencies. Current insight is that although the technology is versatile major research efforts are required for identifying the mechanical, immunological and physico-chemical requirements for successful human application.